Effects of different animal manures on yield quality and nutrient uptake by Mustard CV. Agrani - Zamil, Sheikh Shawkat; Quadir Forhad Quazi, Chowdhury Dr. M.A.H.; Al Wahid, Adnan (BRAC University, 2010)
A pot experiment was carried out at the researcher’s net house of Bangladesh Agricultural University, Mymensingh from November 2003 to February 2004 to find out the effects of different animal manure on yield, quality and nutrient uptake by mustard cv. Agrani. The experiment comprised of two levels of cage system poultry manure, deep litter system poultry manure, cow dung and bio-gas slurry viz. 10 and 20 ton ha-1, one control and one chemical fertilizer @ recommended dose. Cage system poultry manure @ 20 ton ha-1 significantly increased the seed and straw yield of mustard and cow dung showed lower performance. In straw and seed the highest uptake of N, P, K, Ca, Mg and S was obtained from cage system poultry manure @ 20 ton ha-1. Protein and oil content was also found higher in this treatment. Seed yield was found to be significantly and positively correlated with branch and effective pod per plant. Protein and oil contents of mustard seeds were increased with increasing level of animal manures though their effects were not significant. A positive and significant correlation was observed between protein and oil contents of mustard cv. Agrani. The overall results suggest that cage system poultry manure @ 20 ton ha-1 gave best performance among the parameters studied.